2021
DOI: 10.1088/2053-1591/abeeca
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and verification of a biomimetic design model based on fish skin

Abstract: Many biological architectures are Bouligand structures, which comprise uniaxial fiber layers stacked in a periodic helical arrangement and are characterized by high damage resistance. As an effective flexible protective structure, fish skin is a Bouligand structure that protects the body while ensure flexibility during swimming and predation. In this paper, an analytical model inspired by fish skin is established based on previous studies, and the parameters for describing crack growth are determined. Then, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was observed that impact resistance decreases with increase in the helical stacking angle. SEM analysis was also done to find the relevant microstructure, showing the effective resistance of the biological structure against force in the composite (silicone and Kevlar fiber) [89]. Biomimetic armor was tested under dynamic impact using ElectroForce 3300 equipment (TA Instruments) and a ballistic test using a handgun.…”
Section: Fish Experimental Methods Key Discoveriesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that impact resistance decreases with increase in the helical stacking angle. SEM analysis was also done to find the relevant microstructure, showing the effective resistance of the biological structure against force in the composite (silicone and Kevlar fiber) [89]. Biomimetic armor was tested under dynamic impact using ElectroForce 3300 equipment (TA Instruments) and a ballistic test using a handgun.…”
Section: Fish Experimental Methods Key Discoveriesmentioning
confidence: 99%
“…In next step, Kevlar fibers were included in the solidified mold and covered with another part of the mixture, and the same curing process was repeated. Each sample had five layers of fibers and a constant helical angle [89].…”
Section: Other Techniquesmentioning
confidence: 99%